Chasing TIGER: Federal Funding Opportunities and Regional Transportation Planning. (January 2018) - Lowe, Kate; Sciara, Gian-Claudia
Many challenges make it difficult to achieve the collaborative metropolitan transportation planning ideals articulated in federal policy. A central challenge is that metropolitan planning organizations (MPOs) are responsible for identifying and prioritizing region-serving investments, but numerous transportation agencies and local governments typically implement projects and hold the purse strings. New, less restricted sources of funding could exacerbate these challenges, and so we examine the role of MPOs and their plans in local decisions to pursue project funding from the federal Transportation Investment Generating Economic Recovery (TIGER) program. Based on a national survey of MPOs, we find that the local selection of TIGER projects aligns with the federal emphasis on shovel-readiness, but that this criterion still allowed significant latitude for additional factors to shape local project selection. Despite competing factors and limits to regional planning, MPO planning and documents still played a substantial role in the local selection of TIGER projects.